Location of Drip Irrigation Tapes Affects Root Redistribution and Yield of Mature Jujube - LI Zhaoyang; WANG Xingpeng; YANG Yuhui (Guan'gai paishui xuebao, 2021)
【Background】 Flooding irrigation is commonly used to water jujube in Xinjiang. It is not only an inefficient use of the scarce water resources and increases evaporation and leakage, but could also result in soil compaction and secondary soil salinization. Over the past decade, drip irrigation has emerged as an improved alternative to replace flooding irrigation of jujube. 【Objective】 This paper investigates how locations of drip irrigation tapes impact on root redistributions and yield of mature jujube trees. 【Method】 We took jujube trees under long-term flooding irrigation as an example and replaced it with drip irrigation. We compared three locations by laying the drip irrigation tapes at 50 cm (T1), 35 cm (T2) and 20 cm (T3) away from either side of the tree stem, with continuing flooding irrigation taken as the control (CK). In each treatment, we measured the wetted soil zone, root distribution and ultimate yield of the jujube. 【Result】 Changing flooding irrigation to drip irrigation narrowed the wet zone significantly, with the majority of the irrigating water constrained to the root zone. With the distance between drip tape and tree stem increasing, the wetted zone changed from narrow-deep shape to wide-shallow shape, benefiting root growth as a result. Long-term flooding irrigation has made root distribute more uniformly, and two years after change to drip irrigation, the root-length density in the top 0~60 cm soil increased by 32.7% (T1), 31.6% (T2) and 21.4% (T3), respectively, compared to those in CK. Horizontally, T1 and T2 increased root-length density in 0~75 cm soil and T3 increased root-length density in 0~50 cm soil by 20.1%, 24.5% and 25.8%, respectively, compared to CK. Drip irrigation improved yield, with T1 and T2 increasing the yield by 12.9% and 12.5%, at 9 135 kg/hm2 and 9 107 kg/hm2 respectively, compared to CK. 【Conclusion】 Replacing flooding irrigation with drip irrigation not only reduces irrigation amount and increases water use efficiency, but also inhibits vegetative growth and increases the ultimate yield. For jujube production in Xinjiang, laying the drip tapes 30~50 cm from either side of the tree stem is optimal for regulating root growth and improving jujube yield.